Amiodaron ile oluşturulan toksisitede beyaz lahana (brassica oleracea l. var. capitata) ekstraktının sıçan kalp dokusuna etkisi - Hazineci, Hazal (My University, 2016)
.ÖZET Amaç: Aritmi tedavisinde kullanılan amiodaron, birçok organda yan etkiye sebep olabilmektedir. Beyaz lahana (Brassica oleracea L. var. capitata) yurdumuzda ve dünyada yetiştirilen önemli sebzelerden biridir. Literatürde amiodaron ve beyaz lahananın kalp üzerindeki etkisini araştıran bir çalışma bulunmamaktadır. Çalışmamızda amiodaron ve beyaz lahana ekstraktının sıçan kalbi üzerine etkilerinin incelenmesi amaçlanmıştır. GereçveYöntem: Sprague-Dawley cinsi dişi sıçanlar her grupta 8 adet olacak şekilde rastgele seçilerek mısır yağı verilen kontrol grubu; beyaz lahana ekstraktı (500 mg/ kg/ gün) verilen grup; amiodaron (100 mg/ kg/ gün) verilen grup; amiodaron + beyaz lahana sulu ekstraktı verilen grup olarak dört gruba ayrılmıştır. Yedi gün boyunca sıçanlara beyaz lahana ekstraktı ve amiodaron gavaj yolu ile verilmiştir. Amiodaron, beyaz lahana ekstraktı verildikten 1 saat sonra uygulanmıştır. Sekizinci günde hayvanların kalpleri alınarak homojenize edilmiştir. Homojenatta lipit peroksidasyonu (LPO), indirgenmiş glutatyon (GSH), total siyalik asit (TBA) ve protein seviyeleri ile süperoksit dismutaz (SOD), katalaz (CAT), glutatyon-S-transferaz (GST) ve doku faktörü (DF) aktiviteleri incelenmiştir. Sonuçlar istatistiksel olarak değerlendirilmiştir. Bulgular: Amiodaron uygulaması kalp dokusunda LPO ve SA düzeylerini arttırmış, GSH düzeylerini, CAT ve DF aktivitelerini azaltmıştır. SOD ve GST aktivitesini ise anlamlı olmamakla beraber azaltmıştır. Beyaz lahana ekstresinin verilmesi, LPO ve SA düzeylerini azalttı, GSH düzeylerini, SOD, CAT ve GST aktivitelerini ise arttırmıştır. Sonuçlar: Çalışmamızda amiodaron uygulamasının kalp dokusunda LPO ve SA düzeylerini arttırmış olması, amiodaronun toksik etkilerinin serbest radikalleri arttırmasına bağlı olduğunu gösteren çalışmalarla uyumludur. Beyaz lahana amiodaron uygulanan grupta, LPO ve SA düz düzeylerini azaltarak ve antioksidan sistem elemanlarını arttırarak olumlu etki göstermiştir. Sonuçlarımız doğrultusunda, beyaz lahana tüketimi, amiodaronun kalp dokusundaki yan etkilerinin azaltılması için alternatif bir önlem olarak değerlendirilebilir. Anahtar Sözcükler: Kalp, beyaz lahana, amiodaron, oksidan ve antioksidan parametreler, doku faktörü. Effect Of White Cabbage (Brassica Oleracea L. var. capitata) Extract On Rat Cardiac Tissue in Amiodarone Induced Toxicity

Aim: Amiodarone is used to treat arrhythmia and can cause side effects in many organs. White cabbage (Brassica oleracea L. var. capitata) is one of the most important vegetables grown in our country and around the world. There is no study evaluating the effects of amiodarone and white cabbage on heart. This study aimed to examine the effects of amiodarone and white cabbage extract on rats’ heart tissues. Methods: Sprague-Dawley female rats were randomly divided into 4 groups (n = 8) corn oil treated control group; cabbage extract (500 mg / kg / day) treated group; amiodarone (100 mg / kg / day) treated group; amiodarone+aqueous extract of white cabbage treated group. Cabbage extract and amiodarone were given to rats for seven days through gavage. Amiodarone was administered 1 hour after the adminitration of white cabbage extract. Hearts of the animals were removed and homogenized on the eighth day. In homogenates lipid peroxidation (LPO), reduced glutathione (GSH), total sialic acid (TBA), protein levels and superoxide dismutase (SOD), catalase (CAT), glutathione-S-transferase (GST) and tissue factor activities (TF) were examined. The results were analyzed statistically. Results: The application of amiodarone increased LPO and SA levels and decreased GSH levels, CAT and TF activities. SOD and GST activities decreased although not düzeylerini azaltarak ve antioksidan sistem elemanlarını arttırarak olumlu etki göstermiştir. Sonuçlarımız doğrultusunda, beyaz lahana tüketimi, amiodaronun kalp dokusundaki yan etkilerinin azaltılması için alternatif bir önlem olarak değerlendirilebilir. Anahtar Sözcükler: Kalp, beyaz lahana, amiodaron, oksidan ve antioksidan parametreler, doku faktörü. 2.İNGİLİZCE ÖZET Effect Of White Cabbage (Brassica Oleracea L. var. capitata) Extract On Rat Cardiac Tissue in Amiodarone Induced Toxicity ABSTRACT Aim: Amiodarone is used to treat arrhythmia and can cause side effects in many organs. White cabbage (Brassica oleracea L. var. capitata) is one of the most important vegetables grown in our country and around the world. There is no study evaluating the effects of amiodarone and white cabbage on heart. This study aimed to examine the effects of amiodarone and white cabbage extract on rats’ heart tissues. Methods: Sprague-Dawley female rats were randomly divided into 4 groups (n = 8) corn oil treated control group; cabbage extract (500 mg / kg / day) treated group; amiodarone (100 mg / kg / day) treated group; amiodarone+aqueous extract of white cabbage treated group. Cabbage extract and amiodarone were given to rats for seven days through gavage. Amiodarone was administered 1 hour after the adminitration of white cabbage extract. Hearts of the animals were removed and homogenized on the eighth day. In homogenates lipid peroxidation (LPO), reduced glutathione (GSH), total sialic acid (TBA), protein levels and superoxide dismutase (SOD), catalase (CAT), glutathione-S-transferase (GST) and tissue factor activities (TF) were examined. The results were analyzed statistically. Results: The application of amiodarone increased LPO and SA levels and decreased GSH levels, CAT and TF activities. SOD and GST activities decreased although not significant. White cabbage extract decreased LPO, SA levels, increased GSH levels, SOD, CAT and GST activities. Conclusion: In our study, increases in heart tissue LPO and SA levels of amiodarone treated rats are consistent with studies showing that toxic effects of amiodarone is due to the increase of free radicals. White cabbage positively affected heart tissue by decreasing LPO and SA levels and increasing antioxidant system components in amiodarone group. According to our results, cabbage consumption can be considered as an alternative way to reduce the adverse effects of amiodarone on the heart tissue. Heart, white cabbage, amiodarone, oxidant and antioxidant parameters, tissue factori.
Keywords: Biyokimya